35.1k views
2 votes
Suppose a - b = 0a−b=0a, minus, b, equals, 0. Which one of these expressions equals a+ba+ba, plus, b?

User Oleshko
by
5.8k points

2 Answers

2 votes

Answer:

a + b = 2a

or

a + b = 2b

Explanation:

User Shardj
by
6.4k points
2 votes
First we have the following equation:
a - b = 0
We clear one of the variables depending on the other:
a = b
Therefore we have to for the following expression:
a + b
We can substitute one of the variables, obtaining:
a + a = 2a
Equivalently:
b + b = 2b
Answer:
a + b = 2a
or
a + b = 2b
User Vincenzo Lavorini
by
7.0k points